2022
DOI: 10.1080/19585969.2022.2128697
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac vagal activity is associated with gut-microbiome patterns in women—An exploratory pilot study

Abstract: Introduction A functional reciprocity between the gut microbiome and vagal nerve activity has been suggested, however, human studies addressing this phenomenon are limited. Methods Twenty-four-hour cardiac vagal activity (CVA) was assessed from 73 female participants (aged 24.5 ± 4.3 years). Additionally, stool samples were subjected to 16SrRNA gene analysis (V1–V2). Quantitative Insights Into Microbial Ecology (QIIME) was used to analyse microbiome data. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“… 32 A recent pilot clinical trial in women indicated that cardiac vagal activity correlated closely with gut microbiota and the gut-brain axis via the vagal nerve; additionally, vagal activity correlated inversely with inflammatory parameters. 33 Clostridia, Lachnospira, Ruminococaceae, Faecalibacterium, Lactobacillales , and Streptococcaceae were more abundant microbial species in subjects with higher cardiac vagal activity. 33 Therefore, the gut microbiota represents a promising candidate for controlling disease and a noninvasive predictor of prognosis.…”
Section: Gut-brain Axis: Mechanism Of Action and Therapeutic Targets ...mentioning
confidence: 88%
See 1 more Smart Citation
“… 32 A recent pilot clinical trial in women indicated that cardiac vagal activity correlated closely with gut microbiota and the gut-brain axis via the vagal nerve; additionally, vagal activity correlated inversely with inflammatory parameters. 33 Clostridia, Lachnospira, Ruminococaceae, Faecalibacterium, Lactobacillales , and Streptococcaceae were more abundant microbial species in subjects with higher cardiac vagal activity. 33 Therefore, the gut microbiota represents a promising candidate for controlling disease and a noninvasive predictor of prognosis.…”
Section: Gut-brain Axis: Mechanism Of Action and Therapeutic Targets ...mentioning
confidence: 88%
“… 33 Clostridia, Lachnospira, Ruminococaceae, Faecalibacterium, Lactobacillales , and Streptococcaceae were more abundant microbial species in subjects with higher cardiac vagal activity. 33 Therefore, the gut microbiota represents a promising candidate for controlling disease and a noninvasive predictor of prognosis.…”
Section: Gut-brain Axis: Mechanism Of Action and Therapeutic Targets ...mentioning
confidence: 88%
“…Higher parasympathetic activity, which is critical for restorative processes and the primary cause of heart rate variations, is reflected in a larger HRV [ 120 ]. A higher HRV is associated with higher gut microbial diversity and specific species such as L. incertae sedis abundance in the healthy population [ 121 , 122 ]. Exercise training is well known to increase HRV in the healthy population [ 120 , 123 ] and could be linked to an increase in vagal tone that may promote a preferential anti-inflammatory milieu at the intestinal luminal interface [ 52 ].…”
Section: A Healthy Gut Microbiomementioning
confidence: 99%
“…In the subgroup of TRD who continued SSRI's ( n = 19), psilocybin was well-tolerated, with 11 (58%) participants reporting TEAEs, of which a majority (81%) were of mild severity ( COMPASS, 2021 ). Given the role of serotonin in the stimulation of gut motility, it raises interesting questions of whether the diet-MGB axis may have subtle implications for the modulation of transient GI side-effects or autonomic nervous system effects in psychedelic therapy ( Holze et al, 2021 ; Mörkl et al, 2022 ; Olbrich et al, 2021 ).…”
Section: The Gut Microbiota and Adverse Effects Of Psychedelicsmentioning
confidence: 99%